Enrichment of megabase-sized DNA molecules for single-molecule optical mapping and next-generation sequencing. Issue 1 (December 2017) - Łopacińska-Jørgensen, Joanna; Pedersen, Jonas; Bak, Mads; Mehrjouy, Mana; Sørensen, Kristian; Østergaard, Peter; Bilenberg, Brian; Kristensen, Anders; Taboryski, Rafael; Flyvbjerg, Henrik; Marie, Rodolphe; Tommerup, Niels; et al.
Abstract Next-generation sequencing (NGS) has caused a revolution, yet left a gap: long-range genetic information from native, non-amplified DNA fragments is unavailable. It might be obtained by optical mapping of megabase-sized DNA molecules. Frequently only a specific genomic region is of interest, so here we introduce a method for selection and enrichment of megabase-sized DNA molecules intended for single-molecule optical mapping: DNA from a human cell line is digested by the NotI rare-cutting enzyme and size-selected by pulsed-field gel electrophoresis. For demonstration, more than 600 sub-megabase- to megabase-sized DNA molecules were recovered from the gel and analysed by denaturation-renaturation optical mapping. Size-selected molecules from the same gel were sequenced by NGS. The optically mapped molecules and the NGS reads showed enrichment from regions defined by NotI restriction sites. We demonstrate that the unannotated genome can be characterized in a locus-specific manner via molecules partially overlapping with the annotated genome. The method is a promising tool for investigation of structural variants in enriched human genomic regions for both research and diagnostic purposes. Our enrichment method could potentially work with other genomes or target specified regions by applying other genomic editing tools, such as the CRISPR/Cas9 system.